Development of the Information Technology Sector in India: the Role of Government - I. S. Ashmyanskaya (Vestnik MGIMO-Universiteta)
In the article the author analyses the role of government in developing the information technology sector in India, specifically its influence on the three factors that determine the development of the information technology sector: human resources, launch capital and infrastructure. By developing these factors, the Indian government has succeeded in prompt formation and promotion of the information technology sector. The development of human capital is mainly realized by developing public education programs. The establishment of close ties with the Indian diaspora played a crucial role. The diaspora acted as a link for transmission to India of expertise, investment and knowledge. The availability of start-up capital, especially venture capital, is another essential component for the success of the national information technology sector. The conditions created by a government for the development of the institution of venture investment in the country will be of fundamental importance. Thanks to the measures taken by the government of India, venture capital investment has become the main form of financing for start-ups in the information technology sector in India. Developed infrastructure is also an important factor in the development of the information technology sector. In India, a developing country with a vast territory, there was a problem of infrastructure development, and software technology parks became a solution to this problem for companies in the information technology sector. Over the past 20 years, software technology parks in India has evolved so that industrial parks created almost 50% of the total exports of the IT sector in India. The demonstrated state policy can be characterized as the model of state technological entrepreneurship according to which the Indian government played the roles of regulator, producer and promoter in the information technology sector and continues to do so until the present day.